A Spectrum of Unfreedom : Captives and Slaves in the Ottoman Empire - Peirce, Leslie P. (Book collections on Project MUSE., 2021)
"Without the labor of the captives and slaves, the Ottoman empire could not have attained and maintained its strength in early modern times. With Anatolia as the geographic focus, Leslie Peirce searches for the voices of the unfree, drawing on archives, histories written at the time, and legal texts"--